MZ세대의 특성과 언어 사용 연구 - 박순형; Park Soon-hyung (한말연구, 2022)
The purpose of this study is to examine the main characteristics of the MZ generation and the language and characteristics used by the MZ generation in relation to the 2030 generation, which is the mainstay of social interest discussed in various fields. Generation MZ collectively refers to Generation M, Millennial and Generation Z. In this study, based on the fact that generations in their 20s and 30s are grouped together as MZ generations, the Millennial generation is classified into 1980-1995 and Generation Z is classified into 1996-2002. The MZ generation values individual tastes as a "digital native" generation, but knows how to respect diversity. In addition, it is a generation that has a 'Flex' culture but knows how to consume valuable things. In life, they pursue work life balance and have both Yolo and FIRE characteristics, which are concepts that seem to be at the peak of each other. Based on the characteristics that appear in the MZ generation, it can be seen that their language has meme and multi-persona (sub-character) characteristics through buzzwords and new words that appear mainly on SNS. The MZ generation applied and used meme expressions that were popular in various situations, and specific examples showed that words were used in about five ways: abbreviations with only the first syllable (no understanding of meaning), abbreviations with only the first syllable (no understanding of meaning), new words with synthesis, and words with "trans-boundary" methods. It can be seen that the MZ generation uses images in popular photos reflecting the latest trends on the Internet, photos using subtitles in videos, or videos that express what they want to say in a contextual way to sublimate them and use them as a "meme" language. Their preference to express themselves with honest words and actions without hesitation in expressing themselves, but not crossing the line, can also be seen as a characteristic of their language. In the modern society of the digital age, where information is changed in real time, various generations live together. Conflicts between generations have existed in any era since ancient times, but they seem to be intensifying more than ever as the generation gap is extreme in the rapidly changing digital world. Conflicts between generations are only endlessly repeated like Mobius' band with the mindset of "who is right and who is wrong." Through communication with each other, we need to find a solution by understanding, acknowledging, and respecting each other's differences little by little.